Deification for all in and through reformed sacramental liturgy - Bruin, Dieter de (Verbum et ecclesia, 2025)
This article proposes a theological reformation within the Dutch Reformed Church by advocating for the integration of three interrelated concepts: Theosis [deification], a fully sacramental liturgy centred on the Eucharist and Apokatastasis [universal restoration]. It argues that the Dutch Reformed Church’s Missional Theology, rooted in Trinitarian participation, implicitly aligns with the doctrine of Theosis yet requires explicit embrace to fully realise its soteriological potential. By restoring the Eucharist as the heart of worship and reimagining Mission as a bidirectional movement towards the world and back to God, the Dutch Reformed Church can embody a vision of salvation that encompasses all creation. This gesture towards reform seeks to align the Dutch Reformed Church’s practices with its theological suppositions and ignite a broader ecumenical conversation about the nature and scope of divine love and human flourishing. Intradisciplinary and/or interdisciplinary implications: The argument is made that by embracing a version of the doctrine of Theosis and Apokatastasis along with restoring the Eucharist to the centre of worship, the Dutch Reformed Churches and Missional discourse will also become more congruent with its suppositions.